Modified Alvarado scoring system as a diagnostic tool for acute appendicitis at a tertiary care teaching hospital, Central India: a cross sectional study - Kothari, Dilip; Kothari, Archana; Kalantri, Abhishek; Bhambani, Pawan (International Surgery Journal, 2017)
Background: Acute Appendicitis forms an important emergency in the day-to-day surgical practice. It affects human beings irrespective of age, nationality and religion. Early diagnosis and prompt operative intervention is the key for successful management of acute appendicitis. However, the picture of acute appendicitis may not be classical, and in such situations, a policy of early intervention to avoid perforation may lead to high negative appendicectomy rates. Methods: A total of 80 patients were enrolled in the present cross sectional study. Their ages ranged from eleven to 72 years (mean 32.89 ± 15.87). A proforma containing general information about the patient plus eight variables based on the modified Alvarado scoring system was filled. Results: Histological examination confirmed appendicitis in 54 patients (67.5%). The remaining 26 patients were found to have normal appendix giving a negative appendicectomy rate of 32.5% being 36.8% and 28.3% for males and females respectively. Conclusions: This scoring system is easy, simple and cheap complementary aid for supporting the diagnosis of acute appendicitis. MASS can be used effectively in Indian setup to reduce the incidence of negative appendectomies. The patients are not unduly exposed to risks of delay in intervention or significant increase in number of false negative cases.